2013
DOI: 10.1177/1545968312469835
|View full text |Cite
|
Sign up to set email alerts
|

Motor and Premotor Cortices in Subcortical Stroke

Abstract: Background Although functional imaging and neurophysiological approaches reveal alterations in motor and premotor areas after stroke, insights into neurobiological events underlying these alterations are limited in human studies. Objective We tested whether cerebral metabolites related to neuronal and glial compartments are altered in the hand representation in bilateral motor and premotor areas and correlated with distal and proximal arm motor impairment in hemiparetic persons. Methods In twenty participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 57 publications
(92 reference statements)
7
20
0
Order By: Relevance
“…As expected, we found that our patient exhibited significantly lower elbow extension (15.2°) compared to a healthy control group (described previously [14]) who executed the same task (57.9 5.2°). Then, we focused the attention of the participant on this specific impairment decreased elbow extensionduring practice.…”
Section: Case Reportsupporting
confidence: 89%
See 4 more Smart Citations
“…As expected, we found that our patient exhibited significantly lower elbow extension (15.2°) compared to a healthy control group (described previously [14]) who executed the same task (57.9 5.2°). Then, we focused the attention of the participant on this specific impairment decreased elbow extensionduring practice.…”
Section: Case Reportsupporting
confidence: 89%
“…A similar decrease in NAA levels was found in the ischemic core in patients and the outcome predictions based upon the residual NAA in the infarct core have proved accurate [10,11]. More importantly, our recent 1H-MRS studies established a relationship between NAA levels in spared motor areas and behaviorally-relevant neurophysiological brain changes in chronic subcortical stroke [12-14]. Specifically, we found lower levels of NAA, putatively reflecting neuronal metabolic depression [15], in the paretic hand area representation in the ipsilesional motor and premotor areas.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations